Penyuluhan Hak Kekayaan Intelektual (HAKI) Kepada Pelaku UMKM di Kelurahan Bacang Kota Pangkal Pinang - Indinastin Indinastin; Munir Munir; Sugianto Sugianto; Kismiadi Kismiadi; Olivia Rahayu; Supuan Sultan Al Alif; Erlina Erlina; Devo Ferin Alfarizi; Maulana Maulana; R.M. Sheridan Abdalla; Saferius Ndruru; Yandi Yandi (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia often face challenges in protecting their Intellectual Property Rights (IPR), particularly due to limited understanding of trademark, copyright, and product design registration. This lack of legal awareness reduces competitiveness and increases the risk of ownership disputes. This Community Service Program aimed to enhance the legal knowledge and awareness of MSMEs regarding IPR through an interactive counseling activity in Bacang Subdistrict, Pangkal Pinang City. The method included material presentation, interactive discussions, IPR registration simulations, and evaluation using pre-test and post-test. The activity was attended by 25 participants from various business sectors. The results showed a significant improvement in participants’ understanding, as evidenced by the average pre-test score of 43.08 increasing to 77.08 in the post-test, representing a 79% improvement. Beyond knowledge enhancement, participants also demonstrated a shift in mindset, with the majority expressing a commitment to initiate IPR registration steps. These findings confirm that practice-based counseling combined with interactive discussions is effective in increasing MSME legal awareness and supporting the protection of intellectual assets through IPR mechanisms